(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
We take the effective Hamiltonian operator until the four degree[3] and this operator has enabled us to convert from pure gauge theory with group SU(3) with periodic conditions into the quantum mechanics with the group SU(3) with periodic conditions and this mean physically we have converted from the study of an infinite number of particles and of freedom degrees (quarks- gluons-plasma) into study of eight particles (Global) independed of space that mains Twenty-four of freedom degrees and specifically Twenty-four anharmonic oscillators and after that we apply perturbation theory (that of the depend of creation operator and annihilation operator( ) on homogenous modes remaining after quantization of the inhomogenous modes and we have concluded the relations: 1-The time evolution for the ensemble average of global operator square (the color magnetic energy ). 2-Thetime evolution for the ensemble average of impulse operator square (the color electric energy ).